Role of living bacteria and other amendment in early development of maize - Hubert, Klára (Acta Agraria Debreceniensis, 2014)
Different bacteria and wood ash, as a possible micro-nutrient, and liming material, was examined in our experiment on the early growth of corn seedlings.The development of renewing energy resources includes the use of energy grasses and energy forests. The intensive land use in forestry and in agriculture may cause the acidification of soils due to the harvest, or leaching of cations. To maintain the sustainability of soils necessary to maintain it’s the buffer capacity, and pH. Beside the lime the wood ash can is one of the most effective sources to provide the sustainability of intensive land use. The soil born micro organisms play a significant role in the maintenance of soil quality. The bio fertilizer, that contains soil originated bacteria (Azotobacter, and Bacillus sp.), was used in the experiments. The plants release several organic acids by their roots lowering the soil pH, and make more available the sparingly soluble minerals. The amounts of released organic matter depend on stress intensity, as the high pH is. The soil life has a significant role to keep the soil conditions on sustainable level, since there are several similarities in nutrient uptake mechanism between the bacteria and higher plants. Advantageous effects of bio-fertilizer were observed in our experiments.We came to the conclusion that the use of wood ash is recommended instead of lime for the improvement of acidic soils, on the evidence of its pH increasing effect. The wood ash contains several micronutrients in an optimum composition for forestry and agricultural plants. The solubility of heavy metals is very low; therefore there is no risk to use the wood ash in the agriculture and in the horticulture by our experiments. The retardation of growth at higher ash doses can be explained by the modification effect to the soil pH, as far as the original soil pH was pH 6.8, and when ash was given to the soil, the pH increases to 7.8 pH, that is unfavourable for the uptake of most nutrients.